Profil dan Tantangan Guru Profesional Abad 21; Relevansi Pemikiran al-Ghazali dan Zakiah Daradjat - Sofiyah, Siti (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2023)
Teachers play an important role in the educational context, because teachers are at the forefront of providing education and deal directly with students. As students' insight increases, teachers must be able to adapt, both in terms of knowledge and teaching abilities. This research aims to compare the views of Al-Ghazali and Zakiah Daradjat regarding the figure and role of the ideal teacher and their relevance in the 21st century. This qualitative research uses a historical and philosophical approach and inductive, comparative and descriptive data analysis methods. The results of this research show that: Al-Ghazali and Zakiah Daradjat have made a big contribution to building the figure of a teacher. Meanwhile, the contribution of the thoughts of these two figures turns out to be a difference even though they have many similarities. Operationally, the concept can be applied and used as an alternative reference for a teacher today, but it must use a new, contextual and reflective approach